A study on airbone particulates matter (PM10 & PM2.5) exposure assessment in KL Sentral, Kuala Lumpur, symptoms associated with sick building syndrome (SBS) and perceptions on indoor air quality (IAQ) among the building occupants - Normadihah Mohamed Aminuddin (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2012)
Indoor air pollution can be considered as a complex issue, much more than other environmental issues. Poor indoor air quality (IAQ) may affect human health either immediately or for a long term. This study aims to determine the level of IAQ and the effects of particles towards occupants of the office buildings. The objectives of study are (i) to measure the level of airborne particulates that contributes to the IAQ during working hours, (ii) to compare the level of airborne particulates with the existing guidelines and standards of IAQ in Malaysia and other Asian .countries and (iii) to assess the symptoms associated with airborne particulates among the building occupants, which were achieved through primary data collection ( case study or site survey, structured interview and questionnaire survey) and supported by literature reviews. The office buildings selected for the case study are SSM, KTMB and MRCB, KL Sentral. The results showed that the mass concentration level of airborne particulates within the areas has exceeded the allowable limit of O. l 5mg/m3 by Indoor Air Quality (IAQ) Code of Practice, 2005 of the Department of Safety and Health (DOSH), Malaysia and 0.05mg/m3 by the Department of Environmental (DOE) ( outdoor) of 8 hours continuous sampling. Based on the findings, the average percentage of respirable particulates from the total inh!E.able particulates at the lobby and office of MRCB (56%) was higher than the others. This is awful because respirable dust particulates are hazardous as they penetrate into human lungs and will cause severe health effects to the occupants of the building and the public in the long run. This is due to the nearby construction works and high numbers of particulates are generated from various types of vehicles for transportation surrounding KL Sentral. Therefore, the development of Standard for National Ambient Air Quality Guidelines on PM2.5 as one of the crucial parameters is highly recommended.